Non-inferiority of cleavage-stage versus blastocyst-stage embryo transfer in poor prognosis IVF patients (PRECiSE trial): study protocol for a randomized controlled trial - Werner M. Neuhausser; Denis A. Vaughan; Denny Sakkas; Michele R. Hacker; Tom Toth; Alan Penzias (BMC, 2020)
Abstract Background With improvements in in vitro culture techniques there has been a steady shift in practice to transfer embryos at the blastocyst stage (post fertilization day (p.f.d.) 5-7), when embryos reach the endometrial cavity during natural conception. For patients with > 5 zygotes on day 1 of embryo development, fresh blastocyst embryo transfer (ET) increases live birth rates when compared to cleavage stage (p.f.d. 3) transfer. In poorer prognosis patients (≤ 5 zygotes) cleavage stage ET is commonly performed to reduce the risk of cycle cancellation if no embryo survives to the blastocyst stage. However, there is a dearth of randomized controlled trial (RCT) data demonstrating improved live birth rates per cycle for cleavage vs blastocyst stage ET in this subgroup of patients. The hypothesis of the PRECiSE (PooR Embryo Yield Cleavage Stage Versus blaStocyst Embryo Transfer) trial is that blastocyst ET is not inferior to cleavage stage ET with regard to live birth rates per retrieval in poorer prognosis patients. The adoption of routine blastocyst culture for all patients would result in higher rates of single embryo transfers (SET), reduced incidence of multiple pregnancies and simplified laboratory protocols, thereby reducing costs. Methods/design Multicenter, non-inferiority randomized controlled trial (RCT) comparing blastocyst to cleavage stage embryo transfer in poorer prognosis patients with ≤5 zygotes on day 1 after fertilization. The primary outcome is live birth per retrieval. Secondary outcomes include: time to pregnancy, clinical pregnancy, ongoing pregnancy, miscarriage and multiple pregnancy rate (per retrieval). This trial will enroll 658 women with ≤5 zygotes on day 1 at 6 IVF centers over the course of 22 months. Discussion If the hypothesis is proven true, the data from this trial may facilitate the adoption of uniform blastocyst culture in all IVF patients. Trial registration ClinicalTrials.gov Identifier: NCT03764865. Registered 5 December 2019, Protocol issue date: 4 December 2018, Original.